2017
DOI: 10.3389/fnmol.2017.00333
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Nanotubes and Gap Junctions–Their Role in Long-Range Intercellular Communication during Development, Health, and Disease Conditions

Abstract: Cell-to-cell communication is essential for the organization, coordination, and development of cellular networks and multi-cellular systems. Intercellular communication is mediated by soluble factors (including growth factors, neurotransmitters, and cytokines/chemokines), gap junctions, exosomes and recently described tunneling nanotubes (TNTs). It is unknown whether a combination of these communication mechanisms such as TNTs and gap junctions may be important, but further research is required. TNTs are long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(228 citation statements)
references
References 103 publications
(211 reference statements)
7
215
0
1
Order By: Relevance
“…Cancer rarely generates new biology, but instead usually perverts established mechanisms. From this, and given altered phenotype following cytoplasmic transfer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)19), we suggest CPP may contribute to cell differentiation and phenotypic control in other biological settings including: embryogenesis, development, inflammation and wound healing.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Cancer rarely generates new biology, but instead usually perverts established mechanisms. From this, and given altered phenotype following cytoplasmic transfer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)19), we suggest CPP may contribute to cell differentiation and phenotypic control in other biological settings including: embryogenesis, development, inflammation and wound healing.…”
Section: Discussionmentioning
confidence: 86%
“…TNT differ markedly from the transferring cell-projections in the current study. Unlike the transient, fast-moving, short, and branching structures here seen to be mechanically supported by the culture surface or cells; TNT often persist hours, extend long distances, are non-branching, and are suspended free above the culture surface (6,7,12,13,(20)(21)(22). Cytoplasmic transfer via cellprojections in the size range of filopodia seems a novel function.…”
Section: Fine Fib Cell-projections Distinct From Tnt Transferred Fib mentioning
confidence: 85%
See 1 more Smart Citation
“…Intercellular communication within the bone marrow niche is an important element that influences leukemogenesis and the biology of leukemic cells. Previous studies demonstrated the possibility of intercellular communication through the formation of TNTs, thin membrane connections that enable direct communication between cells (Ariazi et al, 2017;Ady et al, 2014;Lou et al, 2012a;Gerdes et al, 2013). We investigated whether these connections can be formed within the leukemia microenvironment and participate in leukemia-stroma cross-talk.…”
Section: Tunneling Nanotubes Are Formed Between CML Cells and Stromalmentioning
confidence: 94%
“…Cellular vesicles (Rustom et al, 2004;Onfelt et al, 2006), organelles (Vallabhaneni et al, 2012;Yasuda et al, 2011;Abounit et al, 2016b;Ahmad et al, 2014), miRNAs , viral particles (Sowinski et al, Nat Cell Biol 2008) and proteins (Schiller et al, 2013;Costanzo et al, 2013) can be actively transported directly from cell to cell, travelling along the actin or microtubule backbone of TNTs. Soon after their discovery, TNTs were recognized as a novel mode of intercellular communication Ariazi et al, 2017;Baker, 2017;Nawaz & Fatima, 2017). They have been found in a plethora of cell types to date, including immune cells (Önfelt et al, 2004;Onfelt et al, 2006), neurons (Gousset et al, 2009), cardiomyocytes (Figeac et al, 2014), endothelial cells (Liu et al, 2014;Yasuda et al, 2010), mesenchymal stromal cells (Pasquier et al, 2013), and cancer cells (Lou et al, 2012b;Thayanithy et al, 2014;Pasquier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%